Nitrogen deposition may increase litter accumulative CO2 release in a subtropical estuarine marsh - Hu, Weifang; Zeng, Congsheng; Tong, Chuan; Li, Guoliang; Lan, Xue; Zhou, Jiacong; Zhang, Meiying; Chen, Yuehmin; Zhang, Linhai (Frontiers in Marine Science, 2022)
Microbial evolution-mediated CO2 from litter has aroused widespread concern, and knowing the factors controlling litter-derived CO2 is important when considering the effects of accumulative CO2 release from litter on the global greenhouse. We conducted a short-term N addition (6, 16, and 24 g N m‒2 yr‒1) experiment in Cyperus malaccensis var. brevifolius (shichito matgrass) litter decomosition. Phospholipid fatty acid (PLFA) method and enzyme method were used to analysis litter microbial community composition and enzymatic activity. During a 220-day decomposition period, there was little effect of the N amendments on litter CO2 evolution rates (9.97‒307.54 μg C g−1 h−1) with a notable exception regarding the increase of the high-N treatment at day 20. The accumulative CO2 release significantly increased after N addition in the medium and late phases. The facilitation effect on accumulative CO2 release by N amendments was more and more obvious over the decomposition time, especially for the low- and intermediate-N treatments. At the end of our experiment, compared with the control treatment, accumulative CO2 release increased 69.75%, 76.62%, and 39.93% for low-, intermediate-, and high-N treatments, respectively. These observations highlight that N deposition could cause high losses of litter C as CO2.